PROBLEMATIKA CALON JAMA’AH HAJI KOTA SUKABUMI TAHUN 2026 PADA KANTOR KEMENTERIAN HAJI KOTA SUKABUMI - Dina Putry Anggriani; Abdul Rohman; Sundari Melayu Sri; Ade Hendra Guna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The organization of the Hajj pilgrimage in Indonesia is the responsibility of the government, which is regulated through various regulations to ensure orderly, safe, and professional services for prospective pilgrims. In practice, the implementation of Hajj services at the regional level is inseparable from various dynamics and problems that arise in society. This study aims to examine the problems faced by prospective Hajj pilgrims in Sukabumi City in 2026 based on observations during the Field Experience Practice (PPL) activities at the Sukabumi City Ministry of Hajj Office from January to March. The method used is a qualitative descriptive approach through direct observation of the Hajj administrative service process and documentation studies of regulations related to the organization of the Hajj pilgrimage in Indonesia. The results of the study indicate that there are several problems that arise in Hajj services, including changes in the number of pilgrim quotas due to new regulations that cause a decrease in the number of departures from more than 200 pilgrims in the previous year to 38 pilgrims in 2026. This condition has an impact on the longer waiting period for departure and has given rise to the phenomenon of cancellation of Hajj portions by some prospective pilgrims. Furthermore, there are issues related to the payment of the Hajj Travel Fee (BPIH). Of the 38 pilgrims, only 18 were able to depart because some prospective pilgrims were unable to pay the fees. The government has offered several alternative solutions, including the option to pay off the fees within five years or five departure calls, as well as a mechanism for canceling the quota by withdrawing the initial deposit. Furthermore, there is a policy of transferring quota numbers to blood relatives under certain circumstances, such as the death of a prospective pilgrim or a permanent illness. Thus, the problems encountered in Hajj services in Sukabumi City are not only related to administrative factors but are also influenced by changes in national policy, the economic conditions of the community, and the Hajj quota management system in Indonesia.